Organizational and economic aspects of management and development of residential real estate market at the local level - Iryna Burkun (Cхід)
In the article the list of organizationally-economic and integral principles of functioning of market of accommodation offers with the purpose of determination of terms of development of economic constituents of region. It is the inalienable constituent of the harmonious functioning of municipal economy. Municipal and regional development contains a market management the municipal real estate.